2001
DOI: 10.1182/blood.v98.13.3809
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cis elements regulate an alternative splicing event at 4.1R pre-mRNA during erythroid differentiation

Abstract: The inclusion of exon 16 in the mature protein 4.1R messenger RNA (mRNA) is a critical event in red blood cell membrane biogenesis. It occurs during late erythroid development and results in inclusion of the 10-kd domain needed for stabilization of the spectrin/actin lattice. In this study, an experimental model was established in murine erythroleukemia cells that reproduces the endogenous exon 16 splicing patterns from a transfected minigene. Exon 16 was excluded in predifferentiated and predominantly include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 45 publications
5
75
0
2
Order By: Relevance
“…This regulated splicing event underlies the production of a functional 4.1R; inclusion of the 21 amino acid peptide encoded by exon 16, at the N-terminus of the 10 kDa spectrin/actinbinding domain of 4.1R is indeed essential to promote high mechanical stability and high deformability of the mature red cell membrane. We have shown that Epononresponsive MEL cells reproduce exon 16-regulated splicing on DMSO induction to erythroid differentiation from either the endogenous pre-mRNA or transfected minigene transcript (Deguillien et al, 2001). More recently, we have observed that Eporesponsive erythroleukemia cells also efficiently regulate this splicing event when induced in culture with either DMSO or Epo (The´oleyre et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This regulated splicing event underlies the production of a functional 4.1R; inclusion of the 21 amino acid peptide encoded by exon 16, at the N-terminus of the 10 kDa spectrin/actinbinding domain of 4.1R is indeed essential to promote high mechanical stability and high deformability of the mature red cell membrane. We have shown that Epononresponsive MEL cells reproduce exon 16-regulated splicing on DMSO induction to erythroid differentiation from either the endogenous pre-mRNA or transfected minigene transcript (Deguillien et al, 2001). More recently, we have observed that Eporesponsive erythroleukemia cells also efficiently regulate this splicing event when induced in culture with either DMSO or Epo (The´oleyre et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Inclusion of exon 16 in mature 4.1R mRNA was assessed by semiquantitative RT-PCR, as previously described (Deguillien et al, 2001;The´oleyre et al, 2004).…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…More recently, we have developed in MEL cells a stable transfection system, which reproduces this regulated splicing pattern, using minigene constructs bearing exon 16. We showed that multiple cis-acting elements, within the exonic and close vicinity intronic sequences, contribute coordinately to exon skipping in predifferentiated cells, and to promote exon inclusion as the cells differentiate (Deguillien et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate exon 16 inclusion, semi-quantitative RT-PCR experiments were performed as detailed previously [33].…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%